A Causal Paradigm of the Antecedents of Organizational Commitment – Case of Loco Pilots of Indian Railways - Khan, S.M. (International Journal of Social Sciences and Management, 2015)
Although several studies have examined organizational commitment in relation to needs satisfaction and work environment, none have investigated causal paradigm and antecedents of measured variables. Using path analysis modeling, this paper takes the first step at closing this literature gap. The direct effect of satisfaction of social needs, citizenship behaviour and recognition at work and work relations on organizational commitment was observed. The cumulative indirect effect of these variables on organizational commitment of Loco Pilots was significant. The results suggest that Indian Railways may need to focus more on these variables in spawning greater commitment among Loco Pilots. Organizational/managerial implications of casual paradigm of the antecedents of organizational commitment suggested. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 214-221 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12553